The Impact of Self-Expandable Transcatheter Aortic Valve Replacement on Concomitant Functional Mitral Regurgitation: A Comprehensive Engineering Analysis - Caballero, Andrés (Struct Heart, 2020)
BACKGROUND: Mitral regurgitation (MR) is present in a large proportion of patients who undergo transcatheter aortic valve replacement (TAVR). However, existing clinical data on the impact of TAVR on early post-procedural MR severity are contradictory. Using a comprehensive computational engineering methodology, this study aimed to evaluate quantitatively the structural and hemodynamic impact of TAVR on aortic-mitral continuity and MR severity in a rigorously developed and validated patient-specific left heart (LH) computer model with aortic stenosis and concomitant functional MR. METHODS: TAVR procedure was virtually simulated using a self-expandable valve (SEV) at three implantation heights. Pre- and post-TAVR LH dynamics as well as intra-operative biomechanics were analyzed. RESULTS: No significant differences in early MR improvement (<10%) were noted at the three implantation depths when compared to the pre-TAVR state. The high deployment model resulted in the highest stress in the native aortic leaflets, lowest stent-tissue contact force, highest aortic-mitral angle, and highest MR reduction for this patient case. When comparing SEV vs. balloon-expandable valve (BEV) performance at an optimal implantation height, the SEV gave a higher regurgitant volume [Formula: see text] than the pre-TAVR model (40.49 vs 37.59 ml), while the BEV model gave the lowest regurgitant volume (33.84 vs 37.59 ml). CONCLUSIONS: Contact force, aortic-mitral angle, and valve annuli compression were identified as possible mechanistic parameters that may suggest avenues for acute MR improvement. Albeit a single patient parametric study, it is our hope that such detailed engineering analysis could shed some light into the underlying biomechanical mechanisms of TAVR impact on MR.